2021
DOI: 10.1515/jbcpp-2021-0279
|View full text |Cite
|
Sign up to set email alerts
|

The complex relationship between physical activity and diabetes: an overview

Abstract: Diabetes mellitus (DM) is a widespread condition, representing a challenging disease to manage. Exercise is being increasingly recommended as part of the therapeutic regimen for DM but the management of different forms of physical activity is difficult for individuals with diabetes, trainers, and physicians. Regular exercise can improve health and well-being, helping individuals to achieve their target lipid profile, body composition, cardio-respiratory fitness, and glycemic goals. People with diabetes tend to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Blood lipids and glucose are also involved in the onset and development of CAD. Higher blood glucose is the hallmark of insulin resistance and type 2 diabetes, while exercise is the basic strategy to combat it [67]. Although previous studies have reported that HIIT significantly decreases fasting blood glucose or postprandial glucose [68,69], systematic reviews have consistently reported a similar effect in lowing HbA1C levels in Type 2 diabetes between HIIT and MICT [70].…”
Section: Discussionmentioning
confidence: 99%
“…Blood lipids and glucose are also involved in the onset and development of CAD. Higher blood glucose is the hallmark of insulin resistance and type 2 diabetes, while exercise is the basic strategy to combat it [67]. Although previous studies have reported that HIIT significantly decreases fasting blood glucose or postprandial glucose [68,69], systematic reviews have consistently reported a similar effect in lowing HbA1C levels in Type 2 diabetes between HIIT and MICT [70].…”
Section: Discussionmentioning
confidence: 99%
“…Our data confirm exercise therapy may represent a strategy to improve the lipid profile, together or as an alternative to the prescription of lipid-lowering drugs [ 34 ]. The underlying mechanism appears to be linked to the increase in the oxidation capacity of lipids by muscles, thanks to the fatty acid-mediated activation of enzymes and transport proteins in the skeletal muscle tissue [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The improved metabolic capacity of muscle tissue also induces the enhancement in insulin sensitivity, thus explaining the significant decrease in blood glucose detected in this group of patients. The validity of structured physical activity on the glycemia control in diabetic patients is also well documented in literature and constitutes one of the main therapeutic modalities of type 2 diabetes [ 9 , 35 ]. In line with these findings, we observed a significant decrease in the average pre- and postintervention blood glucose values in the experimental group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIIT represents a valid alternative to moderate-intensity continuous training (MICT), which is the recommended gold standard in several guidelines ( Garber et al, 2011 ; Santos et al, 2020 ; Thum et al, 2017 ). While continuous exercise at high intensity leads to exhaustion soon, the alternation of high intensity with rest or low-to-moderate intensity blocks allows patients to easily achieve high intensity levels ( Palermi et al, 2021 ). Furthermore, HIIT has been proposed as a time-efficient form of exercise that may overcome motivational barriers associated with traditional MICT ( Fleg, 2016 ).…”
Section: Introductionmentioning
confidence: 99%